2-Chloroadenosine potentiates the alpha 1-adrenergic activation of phospholipase C through a mechanism involving arachidonic acid and glutamate in striatal astrocytes - el-Etr, M (J Neurosci, 1992)
In cultured striatal astrocytes, 2-chloroadenosine, an adenosine analog resistant to adenosine deaminase, although inactive alone, markedly potentiated the activation of phospholipase C induced by methoxamine, an alpha 1-adrenergic agonist. This effect was suppressed by antagonists of either A1 adenosine or alpha 1-adrenergic receptors. An influx of calcium and two distinct G-proteins are involved in this phenomenon since the potentiating effect of 2-chloradenosine was suppressed in the absence of external calcium or when cells were pretreated with pertussis toxin. In addition, arachidonic acid is likely involved in this potentiating effect. This was shown first by examining the effects of inhibitors of phospholipase A2 or arachidonic metabolism, then by examining the action of arachidonic acid on the production of inositol phosphates in either the presence or absence of methoxamine, and finally by measuring the release of arachidonic acid. The sequential activation of phospholipase C and of protein kinase C is required for the 2-chloroadenosine-induced activation of phospholipase A2 since 2-chloroadenosine markedly stimulated phospholipase C activity in the absence of methoxamine when protein kinase C was activated by a diacylglycerol analog. Finally, the enhancing effect of 2- chloroadenosine on the methoxamine-evoked response seems to result from an inhibition of glutamate reuptake into astrocytes by arachidonic acid. Indeed, the potentiating effect of 2-chloroadenosine was suppressed when external glutamate was removed enzymatically and mimicked by either selective inhibitors of the glutamate reuptake process or direct application of glutamate.